The Global Burden of Emerging and Re-Emerging Orbiviruses in Livestock: An Emphasis on Bluetongue Virus and Epizootic Hemorrhagic Disease Virus - Shanta Barua; Eaftekhar Ahmed Rana; M. Asaduzzaman Prodhan; Syeda Hasina Akter; Jully Gogoi-Tiwari; Subir Sarker; Henry Annandale; Debbie Eagles; Sam Abraham; Jasim M. Uddin (Viruses)
Bluetongue virus (BTV) and epizootic hemorrhagic disease virus (EHDV) are vector-borne orbiviruses that pose an emerging threat to livestock, including cattle and sheep. This review summarizes the global distribution, genetic diversity, and key factors driving their spread along with the existing knowledge gaps and recommendations to mitigate their impact. Both viruses cause hemorrhagic disease in susceptible ruminants and are commonly reported in tropical and subtropical regions including North America, Asia, Africa, Oceania, and some parts of Europe. The geographical distribution of these viruses, encompassing 27 BTV and 7 EHDV serotypes, has shifted, particularly with the recent invasion of BTV-3, 4, and 8 and EHDV-8 serotypes in Europe. Several factors contribute to the recent spread of these viruses such as the distribution of virulent strains by the movement of temperature-dependent Culicoides vectors into new areas due to rapid climate change, the reassortment of viral strains during mixed infections, and unrestricted global trade. These diseases cause significant economic impacts including morbidity, mortality, reduced production, high management costs, and the disruption of international trade. Effective prevention and control strategies are paramount and rely on vaccination, vector control using insecticides, and the destruction of breeding sites, husbandry practices including the isolation and quarantine of infected hosts, restriction of animal movement, prompt diagnosis and identification of circulating strains, and effective surveillance and monitoring plans such as the pre-export and post-import screening of semen used for artificial insemination. However, challenges remain with intercontinental virus spread, live vaccines, and the failure of inactivated vaccines to produce protective immunity against dissimilar strains. Significant knowledge gaps highlight the need for a better scientific understanding and a strategic plan to ensure healthy livestock and global food security.